Producing for TV and emerging media a real-world approach for producers - Kellison, Cathrine; Morrow, Dustin; Morrow, Kacey (Routledge, 2021)
"Gain a thorough understanding of the nuanced and multidimensional role producers play in television and emerging media today to harness the creative, technical, interpersonal, and financial skills essential for success in this vibrant and challenging field. Producing for TV and New Media fourth edition is your guide to avoiding the obstacles and pitfalls commonly encountered by new and aspiring producers. This fourth edition has been updated to include: "Focus on Emerging Media" sections that highlight emerging media, web video, mobile format media and streaming media; sample production forms and contracts; review questions accompanying each interview and chapter; interviews with industry professionals that offer practical insight into cutting-edge developments in television and emerging media production. Fresh analysis of emerging media technologies and streaming media markets Written especially for new and aspiring producers with an insight that simply cannot be found in any other book, this new edition of a text used by professors and professionals alike is an indispensable resource for anyone looking to find success as a television or emerging media producer"-- Provided by publisher.